The relationship of hs-CRP, vitronectin and NT-proBNP serum levels with the extent and severity of cardiac complications in patients with organophosphate pesticide poisoning - You-gui, Zhang; Jie, Sun; Ruo-Dong, Han; Yan-Hong, Wang; Gen, Li; Xiu-Xia, Yan (Cellular and Molecular Biology, 2022)
Acute organophosphate poisoning kills tens of thousands of people annually around the world. These substances are widely used as insecticides in homes, industry, and agricultural environments. Due to the ease of access, they can cause accidental or intentional risks of exposure through the skin or respiratory contact. This study aimed to evaluate the serum levels of hs-CRP, Vitronectin, and NT-proBNP and their relationship with the extent and severity of cardiac complications in patients with organophosphate pesticide poisoning. In this descriptive-comparative study, 160 patients were studied with acute organophosphate poisoning. Also, for better comparison, 40 healthy individuals participated in this study. Diagnosis of organophosphate poisoning was based on clinical findings of serum butyrylcholinesterase levels. The hs-CRP measurement was performed by an autoanalyzer (Abbott, model Alcyon 300, USA) with the ELISA hs-CRP kit (The apDia Company, Belgium). Vitronectin (VN) measurements were performed by ELISA method and Glory science human VN kit with Catalog No: 11668. NT-ProBNP serum levels were analyzed by ProBNP assay kit (Roche, Germany) by ECLIA method using Elecsys 2010 Analyzer. The most important variables studied in this study were the electrical activity and conduction system of the heart, PR distance, QTC interval, and T-wave changes. In this study, most of the patients were women and girls (60.78%). The highest percentage of organophosphate poisoning was in the age group of 15-24 years (37.25%). In most cases (78.43%), poisoning was intentional or suicidal. Evaluation of electrophysiological abnormalities of the heart showed that 89 patients (55.62%) had long QTC interval (>450 msec), 43 cases (26.87%) had possible long QTC (431-450 msec), and 28 cases (17.5%) had normal QTC (<430 msec). Only 9.37% of cases (n = 15) showed an increase in P-R distance, which is characteristic of the first-degree ventricular atrial block. Sinus bradycardia occurred in 57 cases (35.62%) and sinus tachycardia in 43 cases (26.87%); in 60 cases (37.5%), the pulse rate was normal. Smooth T-wave changes were observed in 9.8% of patients and reverse T-wave was observed in 17.6%. A long T-wave was not reported in any case. In only two cases (1.25%) was grade 1 ventricular atrial block and grade 2 and 3 blocks were not observed. In general, there was a significant difference in the hs-CRP, vitronectin, and NT-proBNP serum levels between the patient and control groups in all studied variables. These parameters were also related to the extent and severity of the disease.